Pengembangan Modul Berbasis Proyek pada Mata Kuliah Pelengkap Busana - Asiani Abu; Hamidah Suryani (Seminar Nasional LP2M UNM, 2019)
This study aims (1). To find out the development of project-based learning modules in valid fashion complementary courses (2) To find out students' responses to the project-based learning modules in fashion complementary courses This research uses the Research and Development (R&D) method that develops and produces a product with the ADDIE development model. This research was conducted at the Department of Family Welfare Education, Faculty of Engineering, Makassar State University. The subject of the trial was 30 students of the Concentration of Family Welfare Education in the even semester of the 2018 academic year. Valid data and learning modules were obtained through the assessment of the module book. Student response data obtained from student response questionnaire, the results showed that: 1) The results of the validation rating of the project-based learning module in fashion complementary courses reached a mean of 3.3 or valid categories, 2) the results of the student response rating of the project-based learning module in the subject fashion complements reach 91% or get a positive response, so the learning modules developed are suitable for use in the lecture process at the Department of Family Welfare Education, State University of Makassar